2017
DOI: 10.14302/issn.2641-7669.ject-17-1790
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hexane Content in Edible Vegetable Oils Consumed in Iran

Abstract: Solvent residue such as hexane in foodstuff, especially edible oil could be considered as the undesirable substances when exceeds maximum residue limit (MRL). The aim of this study is to determine the hexane content in various brands of edible oils. Totally forty samples (23 brands) of different types of vegetable oils including frying oils (n=14), blended oils (n=13), sunflower oils (n=6), corn oils (n=5) and canola oils (n=2) from Iran´s market were analyzed for hexane content using solid phase microextracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Yousefi et al (2017) investigated n-hexane residues in 40 edible oils collected from the Iranian market and found them in 90% of the samples (36 out of 40), with hexane levels above the limit of quantification (LOQ) in 14 samples. This study showed that most oils contained hexane residues; however, the level in all samples was below the European MRL of 1 mg/kg, namely 0.043 mg/kg, which was found in a commercial rapeseed oil [109]. Olive pomace oil, called Orujo oil in Spain, is obtained by extraction with hexane from the olive residues left after pressing the fruit to produce virgin olive oils.…”
Section: N-hexane Residues In Commercial Productsmentioning
confidence: 78%
“…Yousefi et al (2017) investigated n-hexane residues in 40 edible oils collected from the Iranian market and found them in 90% of the samples (36 out of 40), with hexane levels above the limit of quantification (LOQ) in 14 samples. This study showed that most oils contained hexane residues; however, the level in all samples was below the European MRL of 1 mg/kg, namely 0.043 mg/kg, which was found in a commercial rapeseed oil [109]. Olive pomace oil, called Orujo oil in Spain, is obtained by extraction with hexane from the olive residues left after pressing the fruit to produce virgin olive oils.…”
Section: N-hexane Residues In Commercial Productsmentioning
confidence: 78%
“…Although it is feasible to minimize these concerns with proper precautions, the production of certain foods, such as all organic foods, is restricted from hexane use. There is indeed evidence that hexane residue up to 21 ppm can be found in soy ingredients and in the 1 ppm range in vegetable oils [32,33]. For soy foods, the Food and Drug Administration (FDA) has not set maximum hexane residue limits, but the European Union (EU) prohibits hexane residue levels greater than 10 ppm.…”
Section: Solvent Extractionmentioning
confidence: 99%
“…PPy-NPs/RGO. So, the SPR signals were separately registered for each n-hexane solution, and the SPR signals were analyzed using Fresnel's equations (1), (3), and (5)- (7). The experiment was repeated 10 times to obtain the variation of resonance angle shift with time.…”
Section: Journal Of Sensorsmentioning
confidence: 99%
“…Typically, rotary evaporator and oven are used to eliminate the n-hexane from palm kernel oil. The analytical methods such as Fourier transform infrared spectroscopy (FT-IR) [6] and gas chromatography (GC) [7] are used to measure the concentration of n-hexane. The mentioned methods are complicated, and they depend on chemical knowledge, nonlinear calibration carves, and high cost instrument.…”
Section: Introductionmentioning
confidence: 99%